Bentuk dan Makna Register Bahasa pada Unggahan Penggemar Sepak Bola dalam Akun Twitter - Pradana, Tito Yoga; Ekawati, Mursia; Pradita, Linda Eka (JURNAL KONFIKS, 2025)
Research on the form and meaning of language registers is motivated by interactions among football fans on social media, which reveal linguistic phenomena in the form of the use of specific and unique terms. Terms in the form of words, phrases, or sentences that are used specifically by a particular group constitute a language register. This study aims to define two types of language registers—open and closed—and explain their meanings in football fan interactions. The study uses a descriptive qualitative approach with data from posts on the @idextratime account. The data collection method used is observation and note-taking. Meanwhile, the data analysis techniques used are data reduction, data classification, and content analysis. The results of the study show 98 language registers, consisting of 69 forms of closed registers that are technical and formal in nature, and 29 forms of open registers that are dynamic and informal in nature. Meanwhile, in terms of the meaning of language registers, the data is divided into four categories: playing techniques, playing positions, technical terms, and slang expressions. The meanings of the registers found experience narrowing, broadening, and shifting meanings depending on the context of use. The use of metaphors in the register data found shows differences with language varieties in contexts outside of football.  Therefore, the language register in the football community on social media not only represents a sporting activity, but also embodies the identity of football fans.